An Integrated Multiscale Method for the Characterisation of Active Faults in Offshore Areas. The Case of Sant’Eufemia Gulf (Offshore Calabria, Italy) - Corradino, M.; Pepe, F.; Burrato, P.; Kanari, M.; Parrino, N.; Bertotti, G.; Bosman, A.; Casalbore, D.; Ferranti, L.; Martorelli, E.; Monaco, C.; Sacchi, M.; et al. (Frontiers in Earth Science, 2021)
Diagnostic morphological features (e.g. rectilinear seafloor scarps) and lateral offsets of the Upper Quaternary deposits are used to infer active faults in offshore areas. Although they deform a significant seafloor region, the active faults are not necessarily capable of producing large earthquakes as they correspond to shallow structures formed in response to local stresses. We present a multiscale approach to reconstruct the structural pattern in offshore areas and distinguish between shallow, non-seismogenic, active faults, and deep blind faults, potentially associated with large seismic moment release. The approach is based on the interpretation of marine seismic reflection data and quantitative morphometric analysis of multibeam bathymetry, and tested on the Sant’Eufemia Gulf (southeastern Tyrrhenian Sea). Data highlights the occurrence of three major tectonic events since the Late Miocene. The first extensional or transtensional phase occurred during the Late Miocene. Since the Early Pliocene, a right-lateral transpressional tectonic event caused the positive inversion of deep (> 3 km) tectonic features, and the formation of NE-SW faults in the central sector of the gulf. Also, NNE-SSW to NE-SW trending anticlines (e.g. Maida Ridge) developed in the eastern part of the area. Since the Early Pleistocene (Calabrian), shallow (< 1.5 km) NNE-SSW oriented structures formed in a left-lateral transtensional regime. The new results integrated with previous literature indicates that the Late Miocene to Recent transpressional/transtensional structures developed in an ~E-W oriented main displacement zone that extends from the Sant’Eufemia Gulf to the Squillace Basin (Ionian offshore), and likely represents the upper plate response to a tear fault of the lower plate. The quantitative morphometric analysis of the study area and the bathymetric analysis of the Angitola Canyon indicate that NNE-SSW to NE-SW trending anticlines were negatively reactivated during the last tectonic phase. We also suggest that the deep structure below the Maida Ridge may correspond to the seismogenic source of the large magnitude earthquake that struck the western Calabrian region in 1905. The multiscale approach contributes to understanding the tectonic imprint of active faults from different hierarchical order and the geometry of seismogenic faults developed in a lithospheric strike-slip zone orthogonal to the Calabrian Arc.